Effect of Sales System Effectiveness and Cash Receipts on Internal Control of Receivables at PT Dwi Ananda Mandiri Jakarta - Sari Wulandari; Sari Bulan Tambunan (Universitas Medan Area, 2022)
The purpose of this study is to determine the effect of the effectiveness of the sales and cash receipt system on the internal control of receivables at PT Dwi Ananda Mandiri Jakarta. The population in this study was all leaders and employees of PT. Dwi Ananda Mandiri Jakarta. The samples used were 30 people using purposive sampling techniques. Data collection techniques using questionnaires. Data analysis techniques use classical assumption tests, multiple regression analysis and hypothesis testing. The results showed that the effectiveness of the sales system had a positive and significant effect on the internal control of receivables. The effectiveness of cash receipts has a positive and significant effect on the internal control of receivables.